Organic Matter Removal from Piggery Wastewater in Waste Stabilisation Pond in Nigeria - Bu Okoro; Ne Nwaiwu (Journal of Applied Sciences and Environmental Management)
Four (4) wastewater quality variables: chemical oxygen demand (COD), total solid (TS), total dissolved  solid (TDS), and total suspended solid (TSS) were determined. Analysed samples comprises of raw influent  and effluents entering and leaving the stabilisation ponds. Significant reduction in variables were obtained,  maximum and minimum values obtained for COD were 917mg/l (anaerobic pond), and 13mg/l  (maturation pond). For TS, TDS and TSS, maximum and minimum values obtained were 14,420mg/l, 9,180mg/l, 5,240mg/l and 3,398mg/l, 3,120mg/l, 278mg/l respectively. Removal efficiencies recorded for  parameters in final effluent (maturation pond) were 98.55% (COD), 76.44% (TS), 66.01% (TDS), and 94.69% (TSS) respectively. © JASEM